Answer:
Therefore the Final Solution is x = 2 and y = 7
i.e (2 ,7)
Step-by-step explanation:
Given:
[tex]-2x+y=3[/tex] ...............Equation ( 1 )
[tex]-3x+y=1[/tex] ...............Equation ( 2 )
[tex]y=3x+1[/tex] ..............Equation ( 3 )
To Find:
x = ?
y = ?
Solution:
Substituting Equation ( 3 ) in Equation ( 1) we get
[tex]-2x+3x+1=3\\\\x=3-1\\\\\therefore x =2[/tex]
Now Substituting x = 2 in Equation ( 3 ) we get
[tex]y=3\times 2+1=6+1\\\\\therefore y=7[/tex]
Therefore the Final Solution is x = 2 and y = 7
i.e (2 ,7)